2019
DOI: 10.3390/app9224881
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of the Allelopathic Potential of Rice by Methyl Salicylate Treatment

Abstract: Weed infestation is one of the most severe problems affecting rice production worldwide. Current weed control practices are either costly or pose a threat to the environment. The use of competitive rice genotypes seems to be a promising strategy. The aim of our study was to improve the allelopathic potential of three selected rice genotypes by foliar application of methyl salicylate (MeSA), a signaling molecule eliciting the plant defense response. Aqueous extracts of the shoots and roots of two competitive (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
1
0
2
Order By: Relevance
“…In addition, P deficiency might increase the synthesis of phenolic allelochemicals through oxidative damage in plants [41]. It was reported that salicylic acid-induced stress is capable of activating the production of phenolic allelochemicals in shoots and roots of rice seedlings [45]. These and our findings suggest that the allelopathic potential of rice is induced by P deficiency and associated with the production of phenolic contents.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, P deficiency might increase the synthesis of phenolic allelochemicals through oxidative damage in plants [41]. It was reported that salicylic acid-induced stress is capable of activating the production of phenolic allelochemicals in shoots and roots of rice seedlings [45]. These and our findings suggest that the allelopathic potential of rice is induced by P deficiency and associated with the production of phenolic contents.…”
Section: Discussionsupporting
confidence: 72%
“…The herbicidal efficacy of the two hydrolates is most likely to be ascribed to methyl salicylate, whose role in plant allelopathy has been previously documented [Bi et al. 2007;Patni et al 2019;Asif et al 2021]. However, its interaction (additional or synergistic) with other components such as thymol [Azirak & Karaman, 2008;Nasrollahi et al 2018;Mohammedi, 2021], α-pinene [Luiza Ishii-Iwamoto et al 2012] and 2-propen-1-ol [Ye et al 2016], capable of inhibiting the germination of weed seeds even at low concentrations, is not to be underestimated and could partially explain the different activity between the two hydrolates.…”
Section: Resultsmentioning
confidence: 99%
“…Berdasarkan hasil penelitian Patni et al (2019), kandungan p-hidroksibenzoat pada 3 akar padi dengan varietas yang berbeda menunjukkan lebih rendah dibanding dengan hasil penelitian ini. Konsentrasi phidoksibenzoat dari ketiga varietas tidak mencapai 40 ppm.…”
Section: Hasil Dan Pembahasan Kandungan Asam P-hidroksibenzoat Dan P-...unclassified
“…Kemampuan perbedaan ekstrak akar padi menghambat pertumbuhan E. crus-galli kemungkinan disebabkan oleh jenis dan konsentrasi alelokimia. Salah satu alelokimia padi adalah senyawa kimia dari golongan asam fenolik (Patni et al, 2019;Ho et al, 2020). Asam fenolik dapat meningkatkan spesies oksigen reaktif (ROS) dengan mengurangi aktivitas enzim antioksidan dalam sel (Inderjit et al, 2002).…”
Section: Penghambatan Ekstrak Akar Padi Terhadap Pertumbuhan Echinoch...unclassified